Testing the job demands-resources model for Indian correctional staff job satisfaction - Qureshi, Hanif (International journal of law, crime and justice, 2023)
The job satisfaction of staff is vital for the effective functioning of any organization. Many studies have been conducted that examine the job satisfaction of correctional officers, though mostly in Western nations. To examine job satisfaction in a cross-cultural setting, this study uses survey data from a sample of 163 correctional officers in a prison in the State of Haryana, India. We examine how job demands (perceived dangerousness of the job and role overload) and job resources (instrumental communication, job autonomy, quality supervision, and job variety) affect job satisfaction. The results indicate that all four job resource variables had significant positive associations with job satisfaction, while neither job demand variable was significantly related to job satisfaction. The implications of the study for policy are also discussed.